Childhood disorders and sociodemographic characteristics associated with depression in adults from a Colombian city - Caro-Muriel, Cristina; Álzate-Montoya, Carlos Andrés; Mora-Rocha, Juan Alejandro; Salas-Zapata, Carolina; Sierra-Hincapié, Gloria María (Universidad y Salud, 2023)
Introduction: Emotional and behavioral disorders that begin in childhood lead to adult changes, which have social consequences. Objective: To determine the association of adult depression with childhood onset of mental disorders and other factors in Envigado (Colombia). Materials and methods: A quantitative observational and cross-sectional study was carried out. The sample size was 737 individuals aged between 18 to 65 years. The CIDI-CAPI instrument of the WHO was used. Data processing and analysis was conducted through SPSS v. 21 software from the CES University and Epidat 4.2. Results: The percentage of depression in adults was 10.8%. This figure was 5.6 times greater in the study population that had history of attention deficit hyperactivity disorder (ADHD) compared to individuals who did not have this disorder (OR= 6.62; 95% CI 1.92–22.7). Conclusions: Childhood ADHD increases the probability of depression in the adult population of Envigado, which supports the importance of promoting mental health programs in children in order to prevent adulthood depression.